HUBUNGAN KOORDINASI MATA TANGAN DAN DAYA LEDAK OTOT LENGAN TERHADAP KEMAMPUAN SERVIS ATAS BOLA VOLI PADA SISWA KELAS XI MA PALATTAE - Fadli, Muh; Ogo Darminto, Andi; Ilahi, Rahmat (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The Relationship between Hand-Eye Coordination and Arm Muscle Explosive Power to the Ability of Volleyball Overhead Serve in Class XI MA Palattae Students. Thesis of the Sports Coaching Education Study Program, Faculty of Teacher Training and Education, Muhammadiyah University of Bone, Academic Year 2025. Supervised by supervisor I Andi Ogo Darminto, S.Pd., M.Pd., and supervisor II Rahmat Ilahi, S.Pd., M.Pd. This study aims to identify: (1) the relationship between hand-eye coordination and overhead serve ability in volleyball; (2) the relationship between arm muscle explosive power and overhead serve ability; and (3) the simultaneous relationship between hand-eye coordination and arm muscle explosive power to the ability of volleyball overhead serve in class XI MA Palattae students. The method used in this study is quantitative with a correlational approach. The sampling technique uses the stratified sampling method. The sample taken consists of 25 students from class XI MA Palattae. To measure eye-hand coordination, a tennis ball throwing and catching test was used, while arm muscle explosive power was measured through an overhand Medicine ball throw test, and overhead serve ability was measured by a volleyball service test. Data analysis was carried out using descriptive and inferential statistics, with the help of the SPSS version 30 program. The results of the study showed that: (1) there is a significant relationship between eye-hand coordination and volleyball overhead serve ability of 0.575 with a significance of 0.003 (<0.05), (2) there is a significant relationship between arm muscle explosive power and volleyball assist serve ability of 0.650 with a significance of <0.001, (<0.05), and (3) there is a significant relationship between eye-hand coordination and arm muscle explosive power with volleyball serve ability (p <0.001 <0.05) simultaneously with an R value of 0.739 and an R Square value of 0.546, which means 54.6%. Thus, overall, it can be concluded that hand-eye coordination and arm muscle explosiveness have a significant relationship with students' volleyball overhand serve ability.